Improving ERP Implementation Phase through BPM and BPMN: A Case from Indonesia - Mustofa, Firzainy Jiddan; Okdinawati, Liane; Widjaja, Fransisca Budyanto (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to evaluate and improve the business processes involved in the ERP implementation phase of a local Indonesian provider, with a specific focus on the master data preparation stage. Utilizing an integrated framework combining Business Process Management (BPM), Business Process Model and Notation (BPMN), the Activity-Based Model, and the ESIA method, this research identifies key bottlenecks caused by sequential data input processes and lack of integration among activities. The proposed business process redesign emphasizes parallel data input, document simplification, and automation of verification and validation, which are expected to accelerate implementation time, enhance data accuracy, and optimize operational efficiency. This study contributes empirically to an in-depth business process analysis within the Food and Beverage (F&B) sector and highlights the importance of proper process modelling and targeted automation to address common challenges faced by local ERP providers. Limitations include a focus on a single ERP implementation phase and a single case study, with the redesign not yet tested through simulation. Future research is recommended to expand the scope to other implementation phases, integrate quantitative performance metrics, and utilize simulation software to evaluate the effectiveness of the proposed process redesign.